Memahami Kriteria dan Implikasi Pengamalan Hadis-Hadis Daif Perspektif Yusuf al-Qardhawi - Nafilatul Hoiroh; M. Inul Rizkiy; Fatichatus Sa’diyah (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2025)
Yūsuf al-Qarḍāwī is a contemporary scholar known for his strict approach to the application of ḥadīth ḍa‘īf. He introduced two additional conditions beyond the three established by Ibn Ḥajar al-‘Asqalānī, making a total of five criteria for the application of weak hadiths. These two additional conditions distinguish al-Qarḍāwī’s perspective from that of other scholars. This study focuses on two main issues: first, Yūsuf al-Qarḍāwī’s views regarding the applicability of weak hadiths; and second, the implications of his criteria for the acceptability of such hadiths. This research is qualitative and employs a library-based approach. Data collection was conducted through documentation techniques. The primary sources consist of three works by al-Qarḍāwī: Kayfa nata‘āmal, Thaqāfat al-Dā‘iyah, and al-Muntaqā min al-Targhīb wa al-Tarhīb. The data were analyzed using content analysis, and the results are presented descriptively. The five conditions proposed by al-Qarḍāwī lead to the exclusion of several categories of weak hadiths from practical application, including munkar, matrūk, those that independently prescribe specific actions, and ḥadīth shādh.